Metal complexes of mixed ligands novel 2- Thioxoimidazolidine-4- one derivative and glycine Synthesis, characterization and biological activity - Nuha M. Rashed; Sallal A.H. Abdullaha (Genius Journals, 2021)
The present study, a new derivative of 2- thioxoimidazolidine-4- one (3-{(E)-[(4- bromophenyl)methylidene]amino}-2-sulfanylideneimidaz olidine -4-one) has been synthesized by the reaction of 4- bromobenzaldehyde with thiosemicarbazide then the resulting product reacted with ethylchloro acetate to produce the ligand. This ligand was characterized by elemental analysis ( C.H.N.S) , (FT-IR) spectra, (UV-Vis) spectra and HNMR spectra. This ligand and amino acid have been used in the preparation of mixed ligand complexes using metal ions Cu(II), Ni(II), Co(II), Zn(II), and Cd(II) the synthesized complexes were characterized using all available technique such as, elemental analysis (C.H.N.S), atomic absorption spectroscopy, ( FT-IR) spectra, ( UV-Vis) spectra, conductivity measurement , and magnetic susceptibility. Finally The antibacterial activity of metal complexes have been studied in microorganisms such as Escherichia coli and Staphylococcus haemolyticus
Keywords: Thioxoimidazolidene compounds; metal complexes of thioxoimidazolidine ligands; mixed ligand complexes, amino acid complexes spectral data; antibacterial activity